We can use three rules to rewrite the logarithm:
Power rule:
![\text{ln}(x^p)=p~\text{ln}(x)](https://img.qammunity.org/2021/formulas/mathematics/college/jne8pbtv61tez9sa4hud60j46l3tg94liv.png)
Product rule:
![\text{ln}(xy)=\text{ln}(x)+\text{ln}(y)](https://img.qammunity.org/2021/formulas/mathematics/college/s7krard8cdqm2qshvn8heh6zanpblhkgq0.png)
Quotient rule:
![\text{ln}(x)/(y) = \text{ln}(x)-\text{ln}(y)](https://img.qammunity.org/2021/formulas/mathematics/college/l6yp3unxw4xvw7jz12d7xa51peg1p73u96.png)
Rewrite each part of the expression:
3 In x → ln(x^3)
2 ln y → ln(y^2)
4 ln z → ln(z^4)
According to the product rule, x^3 and y^2 get multiplied. According to the quotient rule, z^4 is being divided.
ln(x^3) + ln(y^2) - ln(z^4) → x^3*y^2/z^4
Therefore, the logarithm as a single quantity is
![\text{ln}(x^3y^2)/(z^4)](https://img.qammunity.org/2021/formulas/mathematics/college/ocezg8ysxhrf715lo8hpl9p1tonueo19gw.png)
Best of Luck!